Measuring functional limitations after venous thromboembolism: Optimization of the Post-VTE Functional Status (PVFS) Scale. Issue 190 (June 2020) - Boon, G.J.A.M.; Barco, S.; Bertoletti, L.; Ghanima, W.; Huisman, M.V.; Kahn, S.R.; Noble, S.; Prandoni, P.; Rosovsky, R.P.; Sista, A.K.; Siegerink, B.; Klok, F.A.
Abstract: Introduction: We recently proposed a scale for assessment of patient-relevant functional limitations following an episode of venous thromboembolism (VTE). Further development of this post-VTE functional status (PVFS) scale is still needed. Methods: Guided by the input of VTE experts and patients, we refined the PVFS scale and its accompanying manual, and attempted to acquire broad consensus on its use. Results: A Delphi analysis was performed involving 53 international VTE experts with diverse scientific and clinical backgrounds. In this process, the number of scale grades of the originally proposed PVFS scale was reduced and descriptions of the grades were improved. After these changes, a consensus was reached on the number/definitions of the grades, and method/timing of the scale assessment. The relevance and potential impact of the scale was confirmed in three focus groups totaling 18 VTE patients, who suggested additional changes to the manual, but not to the scale itself. Using the improved manual, the κ-statistics between PVFS scale self-reporting and its assessment via the structured interview was 0.75 (95%CI 0.58–1.0), and 1.0 (95%CI 0.83–1.0) between independent raters of the recorded interview of 16 focus groups members. Conclusion: We improved the PVFS scale and demonstrated broad consensus on its relevance, optimal grades, and methods of assessing among international VTE experts and patients. The interobserver agreement of scale grade assignment was shown to be good-to-excellent. The PVFS scale may become an important outcome measure of functional impairment for quality of patient care and in future VTE trials. Highlights: Functional limitations are frequent after venous thromboembolism (VTE). We evaluated the previously proposed post-VTE functional status scale (PVFS scale). After modifications, 53 VTE experts reached consensus on all scale aspects. The goal and use of the scale were fully endorsed by patient focus groups. Interobserver agreement of PVFS scale assessment was shown to be good to excellent.